Enzymatic fish protein hydrolysates in finfish aquaculture: a review. (30th July 2020) - Siddik, Muhammad A.B.; Howieson, Janet; Fotedar, Ravi; Partridge, Gavin J.
Abstract: In intensive farming systems, fish are held at high densities, which may increase stress, leading to susceptibility to diseases that result in economic losses. Therefore, effective feeding practices incorporating health‐promoting compounds such as proteins, hydrolysates and bioactive peptides that can stimulate the defence mechanisms of fish and achieve better growth are some of the priorities for sustainable aquaculture development. Globally, the fish processing industries generate and discard a large volume of waste every year, estimated at up to 60% of the harvested biomass. This waste can be converted to value‐added products such as fish protein hydrolysate (FPH) with the addition of various proteolytic enzymes. FPH from fish processing waste including skin, heads, muscle, viscera, liver and bones is a good source of protein, amino acids, peptides and antioxidants and has been found to possess desirable functional and bioactive peptides. A moderate inclusion of FPH in aquafeeds has the potential to improve growth, feed utilization, immune functions and disease resistance of fish. Production of FPH, targeted to more precise molecular weight ranges, has superior functionalities that are in high demand. With interest in FPH as an aquafeed supplement, this review aimed to summarize the source, production processes and functional properties of FPH and the reported impact of FPH in aquafeed supplement on fish growth, survival, feed utilization, immune response and disease resistance. Possible limitations of using FPH and future research potential as an opportunity for the use of processing fish waste are also discussed.